Research on the influence of ecological specialty industry vine tea on farmers' livelihoods in Laifeng County, China - Yuping Xi; Yongdie Yang; Qiyue Zhang; Zhibing Zhang; Zhengli Ha; Zhengli Ha (Frontiers in Sustainable Food Systems)
The development of ecological specialty industries has emerged as a research priority in recent years. Nevertheless, there is a paucity of research that has examined the impact of the interconnection between ecological specialty industries and farmers' livelihoods. To investigate the causal relationship between the local vine tea industry and farmers' livelihoods, a case study incorporating field surveys was conducted in Laifeng County, Hubei Province. This study developed a farm household livelihood indicator system based on a sustainable livelihood analysis framework and employed a binary logit model. The findings indicate that (i) with the booming development of the vine tea industry, farmers' income has increased significantly, and the growth rate of participants is considerably higher than that of non-participants, with the highest growth rate reaching 46%; (ii) the farmers with higher incomes exhibit a greater level of livelihood capital; (iii) farmers' livelihood capitals have an impact on their willingness to participate in the vine tea industry, with varying degrees of influence observed among farmers with different income levels. This research puts forward constructive suggestions for promoting the development of vine tea specialty industry, improving farmers' livelihoods and rural revitalization.